Switzerland : Financial Sector Assessment Program; Technical Note-Supervision and Oversight of Financial Market Infrastructures. (IMF Staff Country Reports; Country Report, 2019)
Financial Sector Assessment Program; Technical Note-Supervision and Oversight of Financial Market Infrastructures.